2014
DOI: 10.3109/02770903.2014.966914
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a questionnaire against clinical assessment in the diagnosis of asthma in school children

Abstract: Based on the good agreement between the questionnaire responses and the clinical assessments, it is concluded that the questionnaire had good validity and served as a useful epidemiological tool. Detailed clinical testing added little additional information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…However, these questionnaires are bigger and more complex and aimed at detecting these diseases and their risk factors in community settings. 69 We identified minimal symptoms (wheeze, breathlessness/cough, and intermittent relief periods) that were sufficient to provide enough accuracy for disease detection. Being short and simple, these questions would be easy to use in busy clinical practice or by trained healthcare workers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these questionnaires are bigger and more complex and aimed at detecting these diseases and their risk factors in community settings. 69 We identified minimal symptoms (wheeze, breathlessness/cough, and intermittent relief periods) that were sufficient to provide enough accuracy for disease detection. Being short and simple, these questions would be easy to use in busy clinical practice or by trained healthcare workers.…”
Section: Discussionmentioning
confidence: 99%
“…69 The sensitivity and specificity reported using these tools ranged between 50 and 96% depending on the criteria used for the diagnosis. The questionnaires for asthma have been tested for assessing prevalence of asthma in the community.…”
Section: Introductionmentioning
confidence: 99%
“…Prevalences in the KiGGS study in the corresponding “7- to 10-years” age group were based solely on parent information. A Norwegian study found high concordance rates between parent information and medical examinations for allergic diseases, whereby, interestingly, simple questions such as “Does your child suffer from asthma?” exhibited higher validity than those relating to specific asthma symptoms [13]. …”
Section: Discussionmentioning
confidence: 99%
“…The single ISAAC question, parent‐reported physician diagnosed asthma, was used as a proxy for physician diagnosis through clinical assessment . Previous studies found the parent‐reported physician diagnosed asthma question had a high sensitivity (88‐96%) and specificity (87‐96%) in children when compared to physician diagnosis, thus was used as the criterion standard in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Many research studies use the parent‐reported physician diagnosed asthma question developed by the International Study of Allergies and Asthma in Childhood (ISAAC) as a proxy for a clinical assessment . Parent‐reported physician diagnosed asthma has been found to have a high sensitivity (88‐96%) and specificity (87‐96%) when compared to a clinical diagnosis in children …”
Section: Introductionmentioning
confidence: 99%